Analysis of Middle School Students' Proficiency of Mathematics Curriculum Achievement Standards - Jihyun Park (Korea Society of Educational Studies in Mathematics, 2020)
The purpose of this study was to examine the outcomes of the National Assessment of Educational Achievement (NAEA) 2015-2018 when the 2009 Revised National Curriculum was applied and suggested for future curriculum revisions. The characteristics of students' academic achievement were analyzed based on the results of evaluating test items developed by the achievement standards of the 2009 Revised National Curriculum. The analysis showed that students' academic achievement was low in the 'Function', 'Probability and Statistics', and 'Geometry' domain. In addition, many achievement standards could be mastered only by the above average group of students. Accordingly, it is necessary to reinforce customized teaching and learning activities in relation to achievement standards which were under achieved. To improve the achievement characteristics, it is necessary to specify detailed achievement standards and to strengthen the linkage between achievement standards.